Human Biomechanical and Cardiopulmonary Responses to Partial Gravity – A Systematic Review - Richter, Charlotte; Braunstein, Bjoern; Winnard, Andrew; Nasser, Mona; Weber, Tobias (Frontiers in Physiology, 2017)
The European Space Agency has recently announced to progress from low Earth orbit missions on the International Space Station to other mission scenarios such as exploration of the Moon or Mars. Therefore, the Moon is considered to be the next likely target for European human space explorations utilising, the Lunar surface twofold: As an operational test bed for further planetary explorations and to conduct research in a unique setting with 1/6th of Earth’s gravity field. Compared to microgravity (µg), only very little is known about the physiological effects of exposure to partial gravity (µg < partial gravity < 1 g). However, previous research studies and experiences made during the Apollo missions comprise a valuable source of information that should be taken into account when planning human space explorations to reduced gravity environments. This systematic review summarizes the different effects of partial gravity (0.1-0.4 g) on the human musculoskeletal, cardiovascular and respiratory system using data collected during the Apollo missions as well as outcomes from terrestrial models of reduced gravity with either 1 g or microgravity as a control. The evidence-based findings seek to facilitate decision making concerning the best medical and exercise support to maintain astronauts’ health during future missions in partial gravity. The initial search generated 1323 publication hits. Out of these 1323 publications, 43 studies were included into the present analysis and relevant data were extracted. None of the 43 included studies investigated long-term effects. Studies investigating the immediate effects of partial gravity exposure reveal that cardiopulmonary parameters such as heart rate, oxygen consumption, metabolic rate and cost of transport are reduced compared to 1 g. Biomechanical studies reveal that ground reaction forces, mechanical work, stance phase duration, stride frequency, duty factor and preferred walk-to-run transition speed are reduced compared to 1 g. Partial gravity exposure below 0.4 g seems to be insufficient to maintain musculoskeletal and cardiopulmonary properties in the long-term. To compensate for the anticipated lack of mechanical and metabolic stimuli some form of exercise countermeasure appears to be necessary in order to maintain reasonable astronauts’ health, and thus ensure both sufficient work performance and mission